Retracted Research: Post-traumatic stress disorder for displaced women in South Darfur camps - Bishara, Iman Abdul Rasoul Muhammad; Khalifa, Yasser Hassan Ahmed (Journal of Educational and Psychological Sciences, 2018)
*This research was retracted on April 14, 2023 The aim of the research was to identify the post-traumatic stress disorder of displaced women in the camps of South Darfur State. The descriptive approach was used by the researchers. The sample consisted of 500 displaced women who were selected by the intentional method. Post-Traumatic Stress Disorder (SPSS). The results of the study were as follows: - There are statistically significant differences in post-traumatic stress disorder among women displaced in South Darfur camps according to demographic research variables Educational level, age, the period of time spent by women displaced in displacement camps) in all dimensions and total kidney except after repeating the feeling of the event, and avoid thinking. .